Pengaruh Penambahan Silase Hasil Samping Pengolahan Ikan Patin Siam (Pangasius hypopthalmus) pada Pakan Terhadap Performa Pertumbuhan Udang Vaname (Penaeus vannamei) - Safir, Muhammad; Bayan, Fara Farial; Mangitung, Septina F.; Rusaini; Rahman, Samsu Adi (Universitas Madako Tolitoli, 2025)
One of the efforts to reduce production costs in raising vaname shrimp is to use low protein feed with the addition of supplements to improve feed quality. Siamese catfish processing by-products in the form of silage have advantages such as a distinctive aroma and high nutrient absorption. The purpose of the study was to determine the addition of silage by-products of Siamese catfish processing to feed on the growth and survival of vaname shrimp. The treatments tested included the addition of Siamese catfish by-product silage to 25% protein feed at a dose of 10% (A), 20% (B), 30% (C), 40% (D) per kg of feed. The test shrimp (weight 2.30 ± 0.19 g) was given 5% of body weight with a frequency of 5 times a day. Maintenance was carried out for 7 weeks in an aquarium measuring 30×25×25 cm3 containing 12 L of water. The results showed that the highest growth was obtained in the addition of catfish by-product silage at a dose of 40% (2.81 g) and the lowest at a dose of 10% (2.00 g) (p<0.05). The lowest feed conversion ratio was in the 30% dose treatment (2.93) compared to the 10% dose (4.09). The survival rate obtained for all treatments ranged from 86.7-93.3%. The use of silage in feed to obtain growth and survival and low feed conversion ratio in vaname shrimp can be done by adding silage at a dose of 30% / kg of feed.